2019
DOI: 10.29267/mxjb.2020.5.1.11
|View full text |Cite
|
Sign up to set email alerts
|

21st century miniguide to fungal biotechnology

Abstract: Realising the biotechnological potential of fungi requires full appreciation of the molecular biology and genetics of this kingdom. We review recent advances in our understanding of fungal genetic structure as it might influence biotechnology; including introns, alternative splicing of primary transcripts, transposons (transposable elements, or TEs), heterokaryosis, ploidy and genomic variation, sequencing, annotation and comparison of fungal genomes, and gene editing. We end by indicating under-researched, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 120 publications
(111 reference statements)
0
9
0
Order By: Relevance
“…Fungi comprise a large and diverse kingdom of eukaryotic organisms morphologically classified as yeasts, filamentous fungi, or dimorphic fungi (Moore et al, 2020;Sánchez et al, 2020). These organisms can be saprotrophs (decomposing dead material), obligated or opportunistic organisms (decomposers, mutualists or pathogens) (Schmit & Mueller, 2007).…”
Section: Fungal Growth and Hyphal Major Componentsmentioning
confidence: 99%
“…Fungi comprise a large and diverse kingdom of eukaryotic organisms morphologically classified as yeasts, filamentous fungi, or dimorphic fungi (Moore et al, 2020;Sánchez et al, 2020). These organisms can be saprotrophs (decomposing dead material), obligated or opportunistic organisms (decomposers, mutualists or pathogens) (Schmit & Mueller, 2007).…”
Section: Fungal Growth and Hyphal Major Componentsmentioning
confidence: 99%
“…Ahuactzin-Pérez et al (2018) found that P. ostreatus degrades and uses as carbon and energy source high concentration (1000 mg/L) of di(2-ethyl hexyl) phthalate, which is a plasticizer that interfere with endocrine systems in mammals and has been detected as contaminant in the environment. The potential for using Pleurotus for pollutant and plastic degradation is discussed by Sánchez et al (2020).…”
Section: Pleurotusmentioning
confidence: 99%
“…On the other hand, fungi have a long association with humanity and have a profound biological and economic impact. Since ancient times, man has consumed wild mushrooms probably delicately, due to their pleasant taste [7]. They have a great nutritional value with a high content of proteins, vitamins, minerals, fibers, trace elements and low/no calories and cholesterol [8].…”
Section: Introductionmentioning
confidence: 99%
“…They have a great nutritional value with a high content of proteins, vitamins, minerals, fibers, trace elements and low/no calories and cholesterol [8]. Mushrooms have been described as a rich source of different bioactive substances such as antibacterial, antifungal, antiviral, antiparasitic, antioxidant, anti-inflammatory, antiproliferative, anticancer, antitumor, cytotoxic, anti-HIV, hypocholesterolemic, antidiabetic, anticoagulant and hepatoprotective compounds, among other [7,8,9]. Of the approximately 14,000 known species, 2,000 are safe for human consumption and about 650 possess medicinal properties [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation